2007
DOI: 10.1038/sj.clpt.6100149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Ingestion of Cranberry Juice on the Pharmacokinetics of Warfarin, Tizanidine, and Midazolam—Probes of CYP2C9, CYP1A2, and CYP3A4

Abstract: Case reports suggest that cranberry juice can increase the anticoagulant effect of warfarin. We investigated the effects of cranberry juice on R-S-warfarin, tizanidine, and midazolam; probes of CYP2C9, CYP1A2, and CYP3A4. Ten healthy volunteers took 200 ml cranberry juice or water t.i.d. for 10 days. On day 5, they ingested 10 mg racemic R-S-warfarin, 1 mg tizanidine, and 0.5 mg midazolam, with juice or water, followed by monitoring of drug concentrations and thromboplastin time. Cranberry juice did not increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 46 publications
4
63
0
1
Order By: Relevance
“…First experiment using a baculovirus expression system showed that CrJ extract inhibited the metabolite production concentration-dependently. A previous report showed that CrJ had moderate inhibitory potential on flurbiprofen hydroxylation by human liver microsomes 5) , which is similar to the present data. The IC50 report than in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…First experiment using a baculovirus expression system showed that CrJ extract inhibited the metabolite production concentration-dependently. A previous report showed that CrJ had moderate inhibitory potential on flurbiprofen hydroxylation by human liver microsomes 5) , which is similar to the present data. The IC50 report than in this study.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, there are reports indicating that CrJ has a minimal effect on the pharmacokinetics and pharmacodynamics of warfarin 5,6) . However, we think that it is too early to reach a conclusion about the effect of CrJ on CYP2C9 activity, because, although CrJ is reported to inhibit metabolism of CYP2C9 substrates 7) , such effect of CrJ has not been sufficiently evaluated in vitro, and thus there are controversial results between in vivo and in vitro findings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that cranberry juice potently inhibits CYP3A and CYP2C9 in vitro (9, 34); however, in vivo studies with probe substrates for CYP2C9 (S-warfarin), (20). Despite the lack of an effect of cranberry juice on the pharmacokinetics of warfarin (20), several case reports have indicated that cranberry juice results in an enhanced antithrombotic effect of warfarin (8,12,23,27,32,33), suggesting a possible pharmacodynamic effect. A number of studies have reported incidences of apple-, orange-, and grapefruit-drug interactions (6,7,21,29).…”
Section: Discussionmentioning
confidence: 99%
“…25 mg) in the absence or presence of steady-state treatment of the drug that has potential to interact with warfarin; the use of a higher single dose of warfarin allows greater potential to detect an interaction as well as reduces the exposure of healthy volunteers to a prolonged period of anticoagulation. In some published studies, the interaction of a drug with warfarin has been assessed by administration of a single lower (10-15 mg) oral dose of warfarin [13,14]. A 7% decrease in S-warfarin AUC could be demonstrated after a single 10-mg dose of warfarin.…”
Section: Introductionmentioning
confidence: 99%